Indian Commercial Surrogacy Arrangements: Feminist Perspectives on Reproductive Choice (International Journal of Innovative Research in Engineering & Management, 2021)
It explores three prominent conceptualizations that are  component of the assessment of commercial surrogacy, including  the commercialization of parenthood, the eroticism of the gift  correlation, and the organization of the surrogate, particularly in  connection to the feminist as well as academic assessment of  surrogacy in India, throughout this essay. Surrogacy continues to  be influenced by powerful rhetorical ideals such as motherhood,  autonomy, and the romanticism of the gift, all of which continue  to affect the research and interpretation of surrogacy. They are  solidified as the key structural settings inside which surrogacy  appears to work as a result of this process. These three themes are  examined in the article's survey of modern published research on  commercialized surrogacy, which examines the academic  interactions with these three conceptions.
Keywords: ART; Commodification; Commercial Surrogacy; Feminist; Motherhood